Risk factors of temperature increase after cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy - Kang, Hui-xia; Ma, Jun-ying; Su, Yan-yan; Kang, Shan; Feng, Bao-jie; Feng, Xiao-bei; Wang, Xu-sha; Lu, Yun-yun (Frontiers in Oncology, 2023)
Background Cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy (CRS-HIPEC) is the standard treatment for patients with peritoneal cancer (PC). Following CRS-HIPEC, patients may also face risks caused by whole body hyperthermia. This study analyzed the incidence of temperature increases following CRS-HIPEC and identified the attendant risk factors. Methods A retrospective analysis was carried out among 458 patients who received CRS-HIPEC at the Fourth Hospital of Hebei Medical University between August 2018 and January 2021. The patients were divided into two groups according to post-HIPEC axillary temperature (≥38°C), with the demographics and the laboratory test results subsequently analyzed and compared, and the risk factors pertaining to temperature increases analyzed using univariate and multivariate logistic regression. Results During CRS-HIPEC, 32.5% (149/458) of the patients with a temperature increase had an axillary temperature of not lower than 38°C, and 8.5% (39/458) of the patients with hyperpyrexia had an axillary temperature of not lower than 39°C. Female gender, gynecological malignancies, type of chemotherapy drug, increased postoperative neutrophil percentage, and a sharp drop in postoperative prealbumin were associated with the incidence of a temperature increase and axillary temperatures of >38°C. Among these factors, the type of chemotherapy drug was identified as an independent risk factor for a temperature increase during CRS-HIPEC. Conclusion By determining the risk factors pertaining to temperature increases during CRS-HIPEC, medical staff can identify the attendant risks among the patients and thus take preventive measures in a timely manner to maintain the patient’s body temperature at a stable level. This suggests that further clinical research should be conducted to build a risk-prediction model for temperature increases following CRS-HIPEC.